2016
DOI: 10.1002/ccd.26856
|View full text |Cite
|
Sign up to set email alerts
|

Closure of very large PDA with pulmonary hypertension: Initial clinical case‐series with the new Occlutech® PDA occluder

Abstract: With the new Occlutech PDA Occluder closure of very large PDAs and PAH is feasible and efficient. The wider pulmonary artery end of the Occlutech PDA Occluder offers enhanced stability and reduces the risk of embolization. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…The higher degree of residual shunting found immediately after device implantation is a feature which has been reported for other devices as well, especially when used to close larger ducts. [713161718] In our opinion, this initial high rate of residual shunting is not a sign of an ineffective device as it does not indicate the long-term success of PDA closure by the device. In our patient population, there were no cases of postinterventional hemolysis or endocarditis during the complete follow-up period, and we did not see further thromboembolic complications apart from one patient with an ischemic stroke with no residual sequelae.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The higher degree of residual shunting found immediately after device implantation is a feature which has been reported for other devices as well, especially when used to close larger ducts. [713161718] In our opinion, this initial high rate of residual shunting is not a sign of an ineffective device as it does not indicate the long-term success of PDA closure by the device. In our patient population, there were no cases of postinterventional hemolysis or endocarditis during the complete follow-up period, and we did not see further thromboembolic complications apart from one patient with an ischemic stroke with no residual sequelae.…”
Section: Discussionmentioning
confidence: 83%
“…Today, the interventionalist has a wide range of occluder types and coils, mostly nitinol-based and self-expanding, to choose from. [2345678] The use of coils has gained popularity due to the advantages of smaller and more flexible introducer sheaths, simple handling, and cost efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The pulmonary artery pressure to aortic pressure ratio (PAP/Ao) was 0.86 at baseline and improved to 0.36 one year after PDA occlusion. There were no reported incidents of device embolization, hemolysis, residual shunt, or obstruction of the adjacent pulmonary artery or aorta .…”
mentioning
confidence: 99%
“…In this issue of Catheterization and Cardiovascular Interventions , Lehner et al have reported the results of a single‐center retrospective study of 8 patients aged 4–16 years, weighing 14–56 kg, who underwent percutaneous occlusion of isolated large patent ductus arteriosus (PDA) in the setting of elevated pulmonary artery pressures. The investigators assessed the safety, efficacy, and technical feasibility of using the Occlutech PDA occluder in such patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation